2014
DOI: 10.1111/jth.12538
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐reactivity tests identify patients at risk of secondary cardiovascular events: a systematic review and meta‐analysis

Abstract: To cite this article: Wisman PP, Roest M, Asselbergs FW, de Groot PG, Moll FL, van der Graaf Y, de Borst GJ. Platelet-reactivity tests identify patients at risk of secondary cardiovascular events: a systematic review and meta-analysis. J Thromb Haemost 2014; 12: 736-47.Summary. Background: Antiplatelet therapy is the standard treatment for the prevention of cardiovascular events (CVEs). High on-treatment platelet reactivity (HPR) is a risk factor for secondary CVEs in patients prescribed aspirin and/or clopido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 61 publications
4
82
2
2
Order By: Relevance
“…However, a considerable number of patients demonstrate HPR. 14,15 Recently, the level of PR inhibition measured by platelet assays has been shown to predict the risk of recurrent thrombotic events following PCI. 16,17 Therefore, the calculation of platelet aggregation is useful for guiding the choice of antiplatelet drugs and individualizing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a considerable number of patients demonstrate HPR. 14,15 Recently, the level of PR inhibition measured by platelet assays has been shown to predict the risk of recurrent thrombotic events following PCI. 16,17 Therefore, the calculation of platelet aggregation is useful for guiding the choice of antiplatelet drugs and individualizing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although various platelet reactivity assays have not been considered accurate or consistent, 17 in separate HAPR analyses using END is defined as an increase in the NIHSS score of ≥1 point, and END 4 is defined as an increase in the NIHSS score of ≥4 points. END and END 4 were more frequently observed in patients in the fourth quartile based on ∆ARU than in patients in the other quartiles (by Pearson χ 2 ; P=0.003 in the END column and 0.009 in the END 4 column, and P for trends=0.003 and 0.007, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, our study focused on the acute period of ischemic stroke. Few studies have focused on this period or on the platelet reactivity after aspirin administration during the first several days after acute ischemic stroke.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…1 Clopidogrel, a P2Y 12 inhibitor, is often the first choice APT added to aspirin, although previous trials have shown that 40% of patients show high platelet reactivity, despite additional clopidogrel treatment. 8 The few trials reporting on high on-clopidogrel platelet reactivity (HCPR) in PAD patients indicate an even higher incidence. 9e11 In some patients, this phenomenon can be caused by a mutation in the genes coding for cytochrome P450 2C19 (CYP2C19) activity, a liver enzyme that converts the clopidogrel prodrug into its active metabolite.…”
Section: Introductionmentioning
confidence: 99%